Safety and Efficacy Endpoints for Mesenchymal Stromal Cell Therapy in Renal Transplant Recipients - J. R. Bank; T. J. Rabelink; J. W. de Fijter; M. E. J. Reinders (Journal of Immunology Research, 2015)
Despite excellent short-term graft survival after renal transplantation, the long-term graft outcome remains compromised. It has become evident that a combination of sustained alloreactivity and calcineurin-inhibitor- (CNI-) related nephrotoxicity results in fibrosis and consequently dysfunction of the graft. New immunosuppressive regimens that can minimize or eliminate side effects, while maintaining efficacy, are required to improve long-term graft survival. In this perspective mesenchymal stromal cells (MSCs) are an interesting candidate, since MSCs have immunosuppressive and regenerative properties. The first clinical trials with MSCs in renal transplantation showed safety and feasibility and displayed promising results. Recently, the first phase II studies have been started. One of the most difficult and challenging aspects in those early phase trials is to define accurate endpoints that can measure safety and efficacy of MSC treatment. Since both graft losses and acute rejection rates declined, alternative surrogate markers such as renal function, histological findings, and immunological markers are used to measure efficacy and to provide mechanistic insight. In this review, we will discuss the current status of MSCs in renal transplantation with a focus on the endpoints used in the different experimental and clinical studies.